Regression Analysis of the Effect of Exports and Imports on Indonesia's Economic Growth in PerspectiveMaqāṣid al-Syarī‘ah - Hendrianto Hendrianto (AL-FALAH : Journal of Islamic Economics, 2026)
This study aims to analyze the influence of exports and imports on Indonesia's economic growth and examine the results from a global perspective. maqāṣid al-syarī‘ah. The study used a quantitative approach with multiple linear regression methods based on time series data for the 2016–2025 period obtained from the Central Statistics Agency (BPS). The analysis was conducted using EViews 12 through t-tests, F-tests, and coefficients of determination (R²). The results of the study indicate that partially exports and imports do not have a significant effect on economic growth. The export variable has a negative coefficient, as does imports with a negative coefficient, but simultaneously they do not have a significant effect, with a relatively low model ability to explain variations in economic growth. In the perspective maqāṣid al-syarī‘ah, this finding shows that international trade has not fully contributed to achieving prosperity (falah), justice (‘adl), and balance (humility). Therefore, policies are needed that are oriented towards increasing the added value of exports, controlling productive imports, and strengthening the domestic sector in order to realize equitable and sustainable economic growth.